Low dose radiotherapy as an effective treatment in a patient with solitary Wegener’s granulomatosis resistant to systemic treatment – case report - Wygoda, Andrzej; Rutkowski, Tomasz; Składowski, Krzysztof; Hejduk, Beata (Contemporary Oncology/Współczesna Onkologia, 2013)
Wegener’s granulomatosis is a rare disease (10 per 1 000 000 new cases per year), etiologically connected with necrotizing vasculitis of small to medium-size vessels. The disease occurs predominantly in the upper respiratory tract, lungs and kidneys, but any organ may be affected during the course of the illness. It may be difficult to diagnose, especially when c-ACNA antibodies (serologic symptom of Wegener’s granulomatosis) are undetectable and chest X-ray is normal. Early diagnosis is crucial for treatment results. Untreated disease may lead to death. Cyclophosphamide used simultaneously with prednisone is the treatment of choice as the first line procedure. Resistance to standard systemic treatment may be a significant problem. New drugs (rituximab, infliximab) are still under clinical investigation, with promising results. Very limited data concerning effectiveness of radiation therapy exist. We present a report of a female patient with solitary form of Wegener’s granulomatosis located in the facial region, who underwent successful radiation therapy with a complete response.